96.8k views
0 votes
Expression equivalent?
8x2 - 5x + 3x(4 - 2x)​

User Timvp
by
4.4k points

2 Answers

4 votes

Answer:

x • (2x + 7)

Explanation:

2.1 Pull out like factors :

4 - 2x = -2 • (x - 2)

Equation at the end of step 2 :

((8 • (x2)) - 5x) + -6x • (x - 2)

Step 3 :

Equation at the end of step 3 :

(23x2 - 5x) + -6x • (x - 2)

Step 4 :

Step 5 :

Pulling out like terms :

5.1 Pull out like factors :

2x2 + 7x = x • (2x + 7)

User Ashwin Parmar
by
4.8k points
5 votes

Answer:

Explanation:

8x² - 5x + 3x(4 - 2x) =8x² - 5x + 3x*4 - 3x*2x

= 8x² - 5x + 12x - 6x²

Now add the like terms

= 8x² - 6x² - 5x + 12x

= 2x² + 7x

User Merab
by
4.6k points